- Thread starter
- #1

#### mitchconnor

##### New member

- Jun 7, 2013

- 2

g(x)=−4x2−5x

f(x)=−3x2+7x−5(g(x))

f(g(−1))=?

First, let's solve for the value of the inner function, g(−1). Then we'll know what to plug into the outer function.

g(−1)=−4(−1)2+(−5)(−1)

I don't understand why they transformed the minus symbol into an addition symbol. This has happened a few times now. Every time I think I get an answer, I get hoodwinked by this change!

Help would be much appreciated.

f(x)=−3x2+7x−5(g(x))

f(g(−1))=?

First, let's solve for the value of the inner function, g(−1). Then we'll know what to plug into the outer function.

g(−1)=−4(−1)2+(−5)(−1)

I don't understand why they transformed the minus symbol into an addition symbol. This has happened a few times now. Every time I think I get an answer, I get hoodwinked by this change!

Help would be much appreciated.

Last edited: